Two Questions to Marxist Anthropology - Chihab El Khachab (tripleC: Communication, Capitalism & Critique)
“Marxist anthropology” is typically understood as a phase within the history of Euro-American anthropology, which is said to have fizzled out in the 1980s. Since some spectres are difficult to chase, however, Marx’s critique of capitalism continues to haunt the discipline’s output, which is not necessarily couched in Marxist language nor inserted in an explicitly Marxist framework. This essay will not diagnose the reasons behind the waning of “Marxist anthropology” according to the discipline’s professional narrative, but it will eschew such boundaries to concentrate on more urgent issues in criticising contemporary capitalism. Two questions are addressed: 1) How can micro- and macro-social scales in social scientific analysis be integrated? and 2) How can we distinguish between conventional ideas and ideologies through which humans guide their lives under capitalism? Anthropology, I argue, can contribute to a strong critique of contemporary capitalism by attending to these questions, which have been integral in Marxist analysis within and beyond the discipline.